Antihyperglycaemic and haematological effects of ethanol extract of Salacia lehmbachii leaf in alloxan-induced diabetic Wistar rats - Godwin Christian Akuodor; Pius Monday Udia; Sylvester Chika Ohadoma; Ifeanyi M. Obi; Anthony Uchenna Megwas; Jane Ugochi Chilaka; Kingsley Chimsorom Chilaka; Francis Vincent Udoh (Shahrekord University of Medical Sciences, 2021)
Introduction: Salacia lehmbachii is used traditionally for the treatment of diabetes mellitus. This study investigated the hypoglycaemic potentials of ethanol leaf extract of S. lehmbachii and its effects on alloxan-induced diabetic rats' haematological parameters. Methods: A total of 36 male Wistar rats including normal, diabetic untreated, and diabetic treated ones were used in this study. Diabetes was induced by a single intraperitoneal injection of 150 mg/kg of alloxan. When confirmed diabetes, the rats were orally administered 100 mg/kg, 200 mg/kg, and 400 mg/kg daily of the leaf extract for 21 days. The blood glucose levels and haematological parameters were determined in diabetic treated rats compared with the controls. Results: The ethanol leaf extract of S. lehmbachii significantly reduced the blood glucose levels of alloxan-induced diabetic rats when compared with the diabetic control (P < 0.01). The extract also significantly (P < 0.01) improved the haematological parameters of treated rats at three doses employed. Conclusion: It can be concluded that the ethanol leaf extract of S. lehmbachii possesses antihyperglycaemic properties and could be considered a potential candidate for the development of new drugs in the treatment of anaemic conditions.